Income Hedging in Asset Allocation Decisions: Examining the Australian Evidence - Kurian, Samuel (My University, 2018)
In this paper, I examine whether income hedging influences asset allocation decisions of Australian households. Using the HILDA survey and characterizing income risk using industry-level variables, I fail to detect robust evidence that income hedging plays a statistically or economically significant role in the allocation decisions of the cross-section of Australian households.
Keywords: Finance -- Assets; Finance -- Expenditure and constraints on expenditure; Finance -- Income (Salary and Wages); Income, wealth and finances; Finance; Income (Salary and Wages); Expenditure and constraints on expenditure; Assets; Income, wealth and finances